2016
DOI: 10.1177/0003702816638281
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical Raw Material Identification Using Miniature Near-Infrared (MicroNIR) Spectroscopy and Supervised Pattern Recognition Using Support Vector Machine

Abstract: Near-infrared spectroscopy as a rapid and non-destructive analytical technique offers great advantages for pharmaceutical raw material identification (RMID) to fulfill the quality and safety requirements in pharmaceutical industry. In this study, we demonstrated the use of portable miniature near-infrared (MicroNIR) spectrometers for NIR-based pharmaceutical RMID and solved two challenges in this area, model transferability and large-scale classification, with the aid of support vector machine (SVM) modeling. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 27 publications
0
13
0
1
Order By: Relevance
“…6d), based on an LVF and 128-pixel InGaAs array, covering 950-1650 nm (10 526-6060 cm -1 ), with a spectral bandwidth (resolution) of <1.25% of center wavelength yielding a resolution of <12.5 nm at 1000 nm). [247][248][249][250] The handheld instruments are powered via their USB interface; typical measurement times are < 1 s. Siesler has compared a laboratory FT-IR and the Viavi MicroNIR 1700 instruments 251 and found that calibrations for both quantitative predictions and qualitative classifications can be transferred successfully from the laboratory instrument to the portable analyzer. He has also compared the performance of several miniature NIR spectrometers for polymer identification (recycling).…”
Section: Linear Variable Filtersmentioning
confidence: 99%
“…6d), based on an LVF and 128-pixel InGaAs array, covering 950-1650 nm (10 526-6060 cm -1 ), with a spectral bandwidth (resolution) of <1.25% of center wavelength yielding a resolution of <12.5 nm at 1000 nm). [247][248][249][250] The handheld instruments are powered via their USB interface; typical measurement times are < 1 s. Siesler has compared a laboratory FT-IR and the Viavi MicroNIR 1700 instruments 251 and found that calibrations for both quantitative predictions and qualitative classifications can be transferred successfully from the laboratory instrument to the portable analyzer. He has also compared the performance of several miniature NIR spectrometers for polymer identification (recycling).…”
Section: Linear Variable Filtersmentioning
confidence: 99%
“…This apparatus incorporates a Linear Variable Filter enabling its size reduction and facilitating the device’s direct attachment to the walls of the expansion vessel or to any other manufacturing apparatus, without using a fiber optic probe that could cause signal attenuation or dispersion. Therefore, the spectrometer is more stable and the measurements performed more reliable [ 37 , 38 , 39 , 40 , 41 ].…”
Section: Methodsmentioning
confidence: 99%
“…20,21 Assim, destaca-se o microespectrômetro portátil na região do infravermelho próximo (MicroNIR), no qual a espectroscopia de vibração é realizada no comprimento de onda de 908 a 1.676 nm (11.013 a 5.967 cm -1 ). [22][23][24] O MicroNIR possibilita monitorar e determinar propriedades das amostras no local de coleta, 25 além de possuir diversas outras vantagens como: curto tempo de análise (alguns segundos); baixo custo de aquisição e operação; baixo consumo de energia; baixo ou nenhum uso de reagentes; pouco ou nenhum tratamento da amostra; alta segurança do analisador; fácil operação e eliminação de fontes de erros devido a transportes de amostras. Associado a métodos quimiométricos, o MicroNIR possibilita estimar várias propriedades, simultaneamente, bem como controlar a qualidade dos produtos.…”
Section: Artigounclassified